Allocolchicinoids bearing a Michael acceptor fragment for possible irreversible binding of tubulin. Issue 6 (4th June 2020) - Sazanova, Ekaterina S.; Gracheva, Iuliia A.; Allegro, Diane; Barbier, Pascale; Combes, Sébastien; Svirshchevskaya, Elena V.; Fedorov, Alexey Yu
Abstract : We describe an attempt to apply the concept of covalent binding towards the highly active allocolchicinoids selected on the basis of SAR analysis of previously synthesized molecules. Abstract : We describe an attempt to apply the concept of covalent binding towards the highly active allocolchicinoids selected on the basis of SAR analysis of previously synthesized molecules. To achieve the irreversible binding of the agent to the cysteine residues of the colchicine site of tubulin protein, we synthesized a number of new allocolchicinoids bearing the acceptor moiety. Some of the new derivatives possess cytotoxic activity against COLO-357, BxPC-3, HaCaT, and HEK293 cell lines in a low nanomolar range of concentrations. A substoichiometric mode of microtubule assembly inhibition was demonstrated. The most active compounds possess close to colchicine general toxicity on mice.